2018
DOI: 10.1093/bjc/azy060
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Policing and the Politics of Patterns

Abstract: Patterns are the epistemological core of predictive policing. With the move towards digital prediction tools, the authority of the pattern is rearticulated and reinforced in police work. Based on empirical research about predictive policing software and practices, this article puts the authority of patterns into perspective. Introducing four ideal-typical styles of pattern identification, we illustrate that patterns are not based on a singular logic, but on varying rationalities that give form to and formalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 33 publications
0
66
0
7
Order By: Relevance
“…In policing and the criminal justice system across an increasing number of countries, AI-powered software generates false positives and biased risk-assessments that lead to new forms of harm and injustices -be it in the form of predictive policing technologies developed by companies like Palantir or software like the notorious COMPAS (Correctional Offender Management Profiling for Alternative Sanctions) (Kaufmann, Egbert, & Leese 2018;Joh 2017Joh , 2019Joh , 2016. These technologies are designed with two aims: to detect the fraudster-imposter-criminal, and to predict crime and risk.…”
Section: Artificial Intelligence Surveillance and Social Sortingmentioning
confidence: 99%
“…In policing and the criminal justice system across an increasing number of countries, AI-powered software generates false positives and biased risk-assessments that lead to new forms of harm and injustices -be it in the form of predictive policing technologies developed by companies like Palantir or software like the notorious COMPAS (Correctional Offender Management Profiling for Alternative Sanctions) (Kaufmann, Egbert, & Leese 2018;Joh 2017Joh , 2019Joh , 2016. These technologies are designed with two aims: to detect the fraudster-imposter-criminal, and to predict crime and risk.…”
Section: Artificial Intelligence Surveillance and Social Sortingmentioning
confidence: 99%
“…These further insights are needed to be able to critically assess their application in policing strategies and law enforcement, and their consequences for social life and surveillance constellations. For these investigations, research designs that combine (a) qualitative in-depth interviews with experts, police officers, programmers, and representatives of software companies with (b) ethnographic observational field studies, as suggested by Kaufmann, Egbert, and Leese (2019), Kaufmann (2019) and Ullrich (2019), promise to be particularly fruitful.…”
Section: Limitations and Outlookmentioning
confidence: 99%
“…Intersecting STS with law and philosophy (Hildebrandt and Rouvroy 2011), communication and media studies (Gillespie 2014), surveillance studies (Kroener and Neyland 2012), and Human Computer-Interaction studies (Suchman 2007), they have successfully shown how the study of algorithms, autonomic computing, software and technological change can provide an entry-point to study power, agency, accountability and human autonomy. In security studies too, it has been shown that the deployment of algorithmic techniques for security entails important political and ethical stakes that should be described and analysed (Amoore and Raley 2017;Aradau and Blanke 2015;Grommé 2016;Kaufmann et al 2019). But digital security technologies may be hard to comprehend.…”
Section: Secrecy and Digital Security Technologiesmentioning
confidence: 99%